Gender differences in hypertension awareness, antihypertensive use and blood pressure control in Bangladeshi adults: findings from a national cross-sectional survey - Muntasirur Rahman; Gail Williams; Abdullah Al Mamun (BMC, 2017)
Abstract Background Bangladesh is facing an epidemiological transition with a growing burden of non-communicable diseases. Traditionally, hypertension and associated complications in women receive less recognition, and there is a dearth of related publications. The study aims to explore gender differences in high blood pressure awareness and antihypertensive use in Bangladeshi adults at the community level. Another objective is to identify factors associated with uncontrolled hypertension among antihypertensive users. Methods Data from the Bangladesh Demographic and Health Survey (BDHS 2011) was analysed. From a nationally representative sample of 3870 males and 3955 females, aged ≥35 years, blood pressure and related information were collected following WHO guidelines. Logistic regression models were used to estimate adjusted odds ratio (AOR) for factors affecting blood pressure awareness, antihypertensive use and uncontrolled hypertension among males and females taking antihypertensive medications. All analyses were weighted according to the complex survey design. Results Women were more likely to have their blood pressure measured (76% vs. males 71%, p < 0.001) and to be 'aware' about their own high BP (55% vs. males 43%, p < 0.001). No gender difference was observed in antihypertensive medication use among those who were aware of their own high BP (females 67%, males 65%, p = 0.39). Non-working females were less likely to use antihypertensive (67% vs. non-working males 77%, p < 0.05). Poor women were worse off compared with poor males in antihypertensive medication use. One-in-three antihypertensive medication users had stage 2 hypertension (SBP ≥160/DBP ≥100 mmHg). Female sex, older age, increased wealth, higher BMI and certain geographical regions were associated with poor blood pressure control among antihypertensive medication users. Conclusions BP check-ups and hypertension awareness were higher among women than men but did not translate into better antihypertensive medication practice. Gender disadvantage and inequity were observed in antihypertensive medication use. Our findings reiterate the importance of sex-disaggregated analysis and reporting. Policy makers should explore the uncontrolled hypertension burden and geographical variations in Bangladesh.